Minerals Beneficiation - Preliminary Report of Massco Circuitron - Discussion - A. E. Craig; W. J. Tait; E. P. McCurdy (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1951)
C. M. Marquard—The problem of the automatic control of a grinding-classification circuit is not nearly as simple as has been indicated and it cannot be universally solved through the application of this device. The sound emanating from a ball mill such as the metallic clink of the balls against the liners can at times be misleading. The fact that the sound level due to the balls hitting the liners may be at a minimum does not necessarily mean that the mill is properly loaded. I have in mind an ore we treat that has a soft talcy gangue. The soft fluffy nature of this material makes the sound from the ball mill a most misleading parameter that is worthless as a means for controlling the amount of ore fed to the mill. In every milling plant there are transportation lags due to the time it takes the ore to travel from the mill bins to the ball mill. In many plants there may be several different transportation lags due to varying distances of bins from ball mill. These transportation lags can most seriously affect the operation of a controller. It has been found that under many circumstances the transportation lags can be so bad as to cause the controller to hunt seriously. Hunting can and in many cases does become so serious as to render automatic control impossible because of the surges it causes. While it is possible to compensate for this type of lag, this apparatus does not lend itself readily to accomplish the required compensation. Further, if there are groups of bins at various distances from the ball mill, compensation for one may not be sufficient or may be too great for another. Each milling plant presents a separate problem. The apparatus as presently described does not appear sufficiently flexible to accomplish this. It should be noted that the load on the classifier rakes is determined by measuring the current input to the rake drive motor. Variations in line voltage will